Cysteine and glutathione concentrations in plasma and bronchoalveolar lavage fluid after treatment with N-acetylcysteine. Issue 1 (January 1991) - Bridgeman, M. M.; Marsden, M.; MacNee, W.; Flenley, D. C.; Ryle, A. P.
Abstract : N-acetylcysteine (600 mg/day) was given to patients by mouth for five days before bronchoscopy and bronchoalveolar lavage to determine whether N-acetylcysteine could increase the concentrations of the antioxidant reduced glutathione in plasma and bronchoalveolar lavage fluid. Bronchoalveolar lavage was performed 1-3 hours (group 2, n = 9) and 16-20 hours (group 3, n = 10) after the last dose of N-acetylcysteine and the values were compared with those in a control group receiving no N-acetylcysteine (group 1, n = 8). N-acetylcysteine was not detected in plasma or lavage fluid. Plasma concentrations of cysteine, the main metabolite of N-acetylcysteine and a precursor of reduced glutathione, were greater in the groups receiving treatment (groups 2 and 3) than in group 1. Cysteine concentrations in lavage fluid were similar in the three groups. Concentrations of reduced glutathione were greater in both plasma and lavage fluid in group 2 than in group 1. These data suggest that N-acetylcysteine given by mouth is rapidly deacetylated to cysteine, with resulting increases in the concentrations of cysteine in plasma and of reduced glutathione in plasma and the airways, which thus temporarily increase the antioxidant capacity of the lung.